2016
DOI: 10.1039/c5cc09879c
|View full text |Cite
|
Sign up to set email alerts
|

Capturing metal-support interactions in situ during the reduction of a Re promoted Co/γ-Al2O3 catalyst

Abstract: The reduction of a Re promoted Co/γ-Al2O3 catalyst was monitored in situ by synchrotron X-ray powder diffraction (XRPD) under H2 environment. Whole powder pattern analysis showed a non-linear expansion of the unit cell of γ-Al2O3 during the reduction process suggesting the diffusion of cobalt cations into the structure of the γ-Al2O3 support material. The cell expansion coincided with the formation of CoO phase. Evidence for the negative effect of the partial pressure of indigenous H2O on the reduction process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 41 publications
0
29
0
Order By: Relevance
“…This temperature range can be correlated with observed intrusion of Co II into the lattice of γ-alumina during the reduction process. 33 A small sharp peak appears only for catalysts on α-alumina, and we consequently ascribe this feature to reduction of rhenium oxide. It has previously been shown that Re as promoter only shifts the second reduction step of cobalt to lower temperatures.…”
Section: Support and Catalyst Characterizationmentioning
confidence: 69%
See 1 more Smart Citation
“…This temperature range can be correlated with observed intrusion of Co II into the lattice of γ-alumina during the reduction process. 33 A small sharp peak appears only for catalysts on α-alumina, and we consequently ascribe this feature to reduction of rhenium oxide. It has previously been shown that Re as promoter only shifts the second reduction step of cobalt to lower temperatures.…”
Section: Support and Catalyst Characterizationmentioning
confidence: 69%
“…32 Intrusion of Co II into the alumna lattice has been observed to occur during reduction. 33 Although γ-Al2O3 is the standard alumina-based catalyst carrier, several transition phases occur during calcination before the thermodynamically stable α-alumina phase is reached. The crystal morphology of alumina is rather complex, and a large number of polymorphs exist and are formed upon dehydration.…”
Section: Introductionmentioning
confidence: 99%
“…As already mentioned, highly dispersed Co-support phases are invisible by electron microscopic techniques meaning that they are not part of the Co PSD obtained by TEM. In situ X-ray diffraction has been used to probe them indirectly through the detection of their lattice expansion 32,62 . Here it is worth mentioning that an in situ XRD approach in the current case would give valuable input.…”
Section: Discussionmentioning
confidence: 99%
“…Exposure of bulk hcp-Co to temperatures above ~420°C has been shown to initiate/trigger transformation to fcc-Co 47,48 . The topic is still a matter of scientific debate and various deviations from this transformation temperature have been reported and related to various factors such as NP size, metal-support interactions and pre-existing concentration of stacking faults [49][50][51] . Here, with in situ TPR-XRD, the transformation from hcp-Co to fcc-Co is followed.…”
Section: Resultsmentioning
confidence: 99%